PENYERAPAN TENAGA KERJA DI DKI JAKARTA - Dimas .; Nenik Woyanti (Jurnal Bisnis dan Ekonomi, 2009)
In Jakarta, the amount of manpower was larger than the number of opportunitiesfor employment. This fact made a serious unemployment problems.The purpose ofresearch was analyzing the influence of GDP, wage and investment on the absorptionof manpower.There were 3 results of research. First, GDP had a positive significanceinfluence on absorption of manpower. Second, wage factor had a negative significantinfluence on. And third, investment had a negative significant influence on. The lastresult was not according with theory, because the most of investors in Jakarta more usecapital-intensive than manpower-intensive.This study suggested the local government to improve economic growth up, tosurmount the disagreement of wage between employee and employer, and to deep-selectto the next of big investors applicant who will plant their large capital in Jakarta.Key words: opportunities fo emplyement, GDP, wage, investment.